Virtual Synchronous Qualitative Data Collection Methods Used in Health and Social Sciences: A Scoping Review of Benefits, Challenges and Practical Insights - Marc-Olivier Dubé; Rabia Sabah Meziane; Anne Hudon; Sabrina Cavallo; Ingrid Verduyckt; Diana Zidarov (International Journal of Qualitative Methods, 2023)
In recent years, we have seen the use of virtual synchronous qualitative data-collection methods grow exponentially, especially within the context of the COVID-19 pandemic. Although several recommendations for researchers conducting in-person interviews and focus groups are available in the scientific literature, they are not necessarily suited for application in a virtual context. To gain a better understanding of current practices and recommendations in virtual synchronous qualitative data collection, we conducted a scoping review. Information obtained from the 70 articles included in this review highlights the main benefits and challenges of virtual data-collection methods in research, compares differences with in-person means of data collection, and provides readers with practical insights for before, during, and after data collection. This comprehensive overview of the existing literature allowed us to outline the theoretical contributions and practical implications of our work as well as provide perspectives for future research. This scoping review can serve as a tool to inform researchers about how best to conduct virtual synchronous qualitative data collection based on other researchers’ prior experiences and the recommendations currently available in the literature.